100 cases in surgery - Gossage, James A. (100 cases., 2014)
This title in the popular 100 Cases series teaches students and junior doctors to recognize important conditions requiring surgical management, and to develop their diagnostic and management skills, in a format that encourages self-directed learning, clinical thinking and problem-solving.